Future Teachers' Spatial Thinking Skills and Attitudes. Issue 4 (3rd July 2016) - Shin, Euikyung E.; Milson, Andrew J.; Smith, Thomas J.
Abstract : The spatial thinking skills and attitudes of geography majors were compared with those of future teachers majoring in elementary education and secondary social studies education. Scores were obtained for each group on two measures: the spatial skills test and the attitude toward spatial thinking inventory. Mean differences were examined based on five factors: major, gender, travel experience, geography courses, and experience using geographic information systems (GIS). For both outcome measures, results showed that the mean scores for elementary education majors were significantly lower than scores from secondary social studies majors and geography majors. Geography majors outperformed both groups of education majors on both measures. Implications for the preparation of geography teachers are discussed.